Schistosoma mansoni Coinfection Attenuates Murine Toxoplasma gondii-Induced Crohn's-Like Ileitis by Preserving the Epithelial Barrier and Downregulating the Inflammatory Response - Pêgo, Beatriz; Martinusso, Cesonia A.; Bernardazzi, Claudio; Ribeiro, Beatriz Elias; de Araujo Cunha, Aline Fernandes; de Souza Mesquita, Jacilene; Nanini, Hayandra F.; Machado, Marcelo Pelajo; Castelo-Branco, Morgana T. L.; Cavalcanti, Marta Guimarães; de Souza, Heitor S. P. (Frontiers in Immunology, 2019)
Background and aims: Mice orally infected with T. gondii develop Crohn’s disease (CD)-like enteritis associated with severe mucosal damage and a systemic inflammatory response, re-sulting in high morbidity and mortality. Previously, helminthic infections have shown thera-peutic potential in experimental colitis. However, the role of S. mansoni in T. gondii-induced CD-like enteritis has not been elucidated. Our study investigated the mechanisms underlying T. gondii-induced ileitis and the potential therapeutic effect of S. mansoni coinfection. Methods: C57BL/6 mice were infected by subcutaneous injection of cercariae of the BH strain of S. mansoni, and 7-9 weeks later, they were orally infected with cysts of the ME49 strain of T. gondii. After euthanasia, the ileum was removed for histopathological analysis; staining for goblet cells; immunohistochemistry characterizing mononuclear cells, lysozyme expression, apoptotic cells and intracellular pathway activation; and measuring gene expres-sion levels by real-time PCR. Cytokine concentrations were measured in the serial serum samples and culture supernatants of the ileal explants, in addition to myeloperoxidase (MPO) activity. Results: T. gondii-monoinfected mice presented dense inflammatory cell infiltrates and ulcer-ations in the terminal ileum, with abundant cell extrusion, apoptotic bodies and necrosis; these effects were absent in S. mansoni-infected or coinfected animals. Coinfection preserved gob-let cells and Paneth cells, remarkably depleted in T. gondii-infected mice. Densities of CD4- and CD11b-positive cells were increased in T. gondii- compared to S. mansoni-infected mice and controls. MPO was significantly increased among T. gondii-mice, while attenuated in coinfected animals. In T. gondii-infected mice, the culture supernatants of the explants showed increased concentrations of TNF-alpha, IFN-gamma, and IL-17, and the ileal tissue revealed increased expression of the mRNA transcripts for IL-1 beta, NOS2, HMOX1, MMP3, and MMP9 and activation of NF-kappa B and p38 MAPK signaling, all of which were coun-terregulated by S. mansoni coinfection. Conclusion: S. mansoni coinfection attenuates T. gondii-induced ileitis by preserving mucosal integrity and downregulating the local inflammatory response based on the activation of NF-kappa B and MAPK. The protective function of prior S. mansoni infection suggests the in-volvement of innate immune mechanisms and supports a conceptually new approach to the treatment of chronic inflammatory diseases, including CD.